1975
DOI: 10.1093/jnci/55.5.1129
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Mediated Immune Responses to Transplanted Tumors in Mice Chronically Exposed to Cigarette Smoke 2

Abstract: C57BL and BALB/c mice were exposed to fresh cigarette smoke for 7-8 minutes per day for varying periods up to 30 weeks before subcutaneous or intratracheal inoculation of viable tumor cells. The growth rates of subcutaneous tumors in the mice exposed to smoke were significantly higher than those of controls and more lung metastases were noted. Enhanced tumor growth rates in the respiratory tracts of smoke-exposed mice were evidenced by the markedly increased death rates in these animals after the intratracheal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…The contribution of smoking-related comorbidities had been questioned [16,30]. In addition to factors of higher prevalence of aggressive squamous cell carcinoma and greater frequency of post-treatment complications in respiratory systems [31], the biologic malignancy of the primary lesion related to gene mutation, a trend of higher occurrence rate of second malignancies due to clonal genetic alterations in the respiratory epithelium, and a decreased immune surveillance of the airways can mediate poorer prognosis in NSCLC patients who have ever smoked [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of smoking-related comorbidities had been questioned [16,30]. In addition to factors of higher prevalence of aggressive squamous cell carcinoma and greater frequency of post-treatment complications in respiratory systems [31], the biologic malignancy of the primary lesion related to gene mutation, a trend of higher occurrence rate of second malignancies due to clonal genetic alterations in the respiratory epithelium, and a decreased immune surveillance of the airways can mediate poorer prognosis in NSCLC patients who have ever smoked [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Several biological mechanisms could theoretically contribute to the results of our study. It has been reported that smoking causes a decrease in systemic and local immunity in the airways [17][18][19]. It has also been shown that genetic changes similar to those found in lung cancers could be detected in nonmalignant bronchial epithelium of current and former smokers [20][21].…”
Section: Discussionmentioning
confidence: 99%
“…We categorized smoking as follows: consistent smokers (smoked in two consecutive visits); consistent minimal or non-smokers (smoked <1 cigarette per day in two consecutive visits); recent quitters (smoked in the last visit but stopped smoking in the current visit); and new/relapsed smokers (not smoked in the last visit but started or resumed smoking in the current visit). The categorization was based on data from previous studies which suggest that the effect of smoking on the immune system is acute (Tollerud et al,1989Hersey, Prendergast, & Edwards, 1983; Sunyer et al, 1996), with induction period of about five weeks (Thomas, Holt, & Keast, 1975) to 10 weeks (Chalmer, Holt, & Keast, 1975), and lasts for about six to 35 weeks since quitting (Thomas, Holt, & Keast, 1975; Miller, Goldstein, Murphy, & Ginns, 1982; Radloff, 1977). Since the time elapsed between the last HIV-ALC visit to the first HIV-LIVE visit was too long (range one month to 66 months) for some of the subjects enrolled in both cohorts, this secondary analysis was restricted to subjects who participated in HIV-LIVE.…”
Section: Design and Methodsmentioning
confidence: 99%